Static theoretical investigations of organic redox active materials for redox flow batteries - Zaichenko, Aleksandr; Achazi, Andreas J; Kunz, Simon; Wegner, Hermann A; Janek, Jürgen; Mollenhauer, Doreen; Justus Liebig University Giessen (My University, 2023)
New efficient redox flow batteries (RFBs) are currently of great interest for large-scale storage of renewable energy. Further development requires the improvement of the redox active materials. Quantum chemical calculations allow the screening of large numbers of redox active molecules for required static molecular properties. In particular, redox potentials are calculated in high-throughput studies. In addition, calculations of solubility and reactivity and in-depth electronic structure analysis are performed for smaller numbers of molecules. In this review, we provide an overview of the static theoretical investigations carried out on the known classes of molecules that are considered as redox active materials in RFBs. We will focus on electronic structure methods such as density functional theory and wave function-based methods. Furthermore, investigations using the increasingly important machine learning techniques are presented. For each class of redox active molecules considered, significant theoretical results are presented and discussed. In addition, the different quantum chemical approaches used are examined, in particular with regard to their advantages and limitations. Another focus of this review is the comparison of theoretically predicted results with available experimental studies. Finally, future challenges and trends in the theoretical studies of redox active materials are highlighted.
Keywords: ddc:540